Pengaruh Kapabilitas Dinamik Dan Kualitas Layanan Pendidikan Terhadap Minat Masyarakat Di Madrasah Ibtidaiyah DDI 373 Paredeang Kabupaten Polewali Mandar - Sapri Sapri; Paisal Syam; Berlian Berlian (ILIN Institute, 2022)
This study aims to determine whether dynamic capabilities and quality of educational services affect public interest. By using the SPSS Version 25.0 method, there were 62 respondents who were used as samples in this study, namely the parents of students from Madrasah Ibtidaiyah DDI 373 Paredeang. The types of data used in this study are primary and secondary data. Data collection techniques were carried out by distributing questionnaires to the research sample. T-test analysis is used to test in this study. The results of this study indicate that (1) Dynamic Capabilities have a significant effect on public interest. (2) The quality of education services has a significant effect on public interest. And F test analysis is used to test the dynamic capabilities and quality of education services. The results of this study indicate that the dynamic capability and quality of education services simultaneously have a significant effect on public interest in Madrasah Ibtidaiyah DDI 373 Paredeang